The Boundary between Scotland and England in the Portolan Charts - Andrews, Michael C (Proceedings of the Society of Antiquaries of Scotland, 1926)
These early nautical maps confine their attention almost exclusively to coastal features, seaports and islands. Political boundaries of countries, states, and kingdoms are altogether omitted, and even their natural frontiers are seldom indicated. The borderland between Scotland and England appears, however, to be one of the exceptions to this rule. This representation takes different forms in the work of different cartographical schools, executed at different dates.